Best Practices Selection of Consultants - Planning Commission (Planning Commission, 2009)
The Eleventh Five Year Plan recognises that the deficit in infrastructure is a major constraint in achieving the projected growth rate of 9 per cent in GDP and that public sector resources are insufficient to meet the investment requirements. It is, therefore, envisaged that about 30 per cent of the projected investment during the Eleventh Five Year Plan would be sourced from private capital, mainly through Public Private Partnerships (PPPs). The process of structuring PPP projects is complex and the requisite expertise is not available within the government. Nor do project authorities have the time and staff resources that go into fine-tuning the documentation of PPPs. It is, therefore, necessary to rely on consultants for securing financial.
Planning Commission Government of India
Planning Commission Government of India